Concentration of Hydrogen Peroxide by Batch Distillation Column - H. sulaymon, Abbas; H.A l-Karaghouli, Abdul-Rezzak; I. Ghulam, sattar (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
An investigation was conducted to study the concentration of hydrogen peroxide by vacuum distillation. The effect of the process variables (such as vacuum pressure, reflux ratio, time of distillation, and packing height of the column used in the distillation process) on the concentration of hydrogen peroxide were investigated. During the third stage of distillation (95 wt.%) concentration was obtained. Box-Wilson central composite rotatable design is used to design the experimental work for the mentioned variables. It was found that the concentration of hydrogen peroxide increases with Increasing vacuum pressure, decreasing reflux ratio, increasing the time of distillation and increasing the packing height. The second order polynomial regression analysis of the objective response (concentration of hydrogen peroxide). with respect to the four variable, using statistical program gave the following equations: Y1 = 54.87 - 0.27 P - 81.45 R .+ 16.36 t + 0.69 H + 55.67 R2 - 0.0035 H2 Y2 = 104.04 - 0.44 P - 140.62 R + 19.8 t + 0.211 H + 0.0018 P+ 105.25 R2-3.33 r Y3 = 83.79 - 0.18 P - I 9.04 R + I J.14 t - 0.094 H - 0.0047 P 2 - 26.78 R2 - 2.78 t2